Impaired discrimination learning in interneuronal NMDAR-GluN2B mutant mice. Issue 9 (17th June 2015) - Brigman, Jonathan L.; Daut, Rachel A.; Saksida, Lisa; Bussey, Timothy J.; Nakazawa, Kazu; Holmes, Andrew
<x xml:space="preserve">Abstract</x> Previous studies have established a role for N-methyl-D-aspartate receptor (NMDAR) containing the GluN2B subunit in efficient learning behavior on a variety of tasks. Recent findings have suggested that NMDAR on GABAergic interneurons may underlie the modulation of striatal function necessary to balance efficient action with cortical excitatory input. Here we investigated how loss of GluN2B-containing NMDAR on GABAergic interneurons altered corticostriatal-mediated associative learning. Mutant mice (floxed-GluN2B×Ppp1r2-Cre) were generated to produce loss of GluN2B on forebrain interneurons and phenotyped on a touchscreen-based pairwise visual learning paradigm. We found that the mutants showed normal performance during Pavlovian and instrumental pretraining, but were significantly impaired on a discrimination learning task. Detailed analysis of the microstructure of discrimination performance revealed reduced win→stay behavior in the mutants. These results further support the role of NMDAR, and GluN2B in particular, on modulation of striatal function necessary for efficient choice behavior and suggest that NMDAR on interneurons may play a critical role in associative learning.